Diastereoselective and general route to 5-amino-5-deoxysugars: influence of C-3 substitution on the addition of amines to C-5 of vinyl sulfone-modified Hex-5-enofuranosyl carbohydrates - Das, Indrajit; Pathak, T.; Suresh, C. G. (Journal of Organic Chemistry, 2005)
In the synthesis of vinyl sulfone-modified hex-5-enofuranosides, the E/Z ratios of the products are influenced by the stereoelectronic property of a group present at the C-3 position. This observation has been utilized to influence the diastereoselectivity of addition of amines to C-5 of vinyl sulfone-modified hex-5-enofuranosides, which are efficient Michael acceptors. The stereoelectronic effect of OMe attached to the beta-face of C-3 (gluco derivative) is sufficient to impose diastereoselectivity overwhelmingly in favor of L-ido-aminosugars when the Michael acceptor is reacted with both primary and secondary amines. 3-O-Benzylated gluco derivative is also effective in producing L-ido-aminosugars but only in reactions with primary amines. The selectivity is lost when an allo derivative with OBn at the alpha-face of C-3 is used. Selected products were desulfonated to establish this new approach as a general and versatile strategy for accessing 5-amino-5-deoxysugars.